Identification of Extension Methods Based on Local Wisdom to Increase Public Awareness and Understanding of Antimicrobial Control - Mashur; Kholik Kholik; Dina Oktaviana; Muhammad Munawaroh; Muhammad Rama Imam Saputra; Siti Nurus Sa’diyah (IPB University, 2021)
The number of people experiencing antimicrobial resistance continues to increase from year to year it can be a global threat to public health and animal health that can have an impact on the sustainability of the agricultural sector, food security, and environmental security. One of the contributing factors is the lack of public awareness and understanding of the dangers of antimicrobial resistance. For that, we need efforts to increase outreach activities to the community. This study aims to identify the most effective local wisdom- based extension methods for increasing public awareness and understanding of antimicrobial control. The research was conducted using a survey method from September to December 2020 in 10 districts/cities in West Nusa Tenggara. The number of respondents was 71 people determined by positive random sampling. Data were analysis descriptively based on frequency distribution data. The results showed that there were 45 types of extension media that could be used to convey information on antimicrobial control, namely: media extension based on local wisdom as much as 59.15%; conventional extension media 35.21% and modern extension media 5.64%. Extension methods that are effectively applied are extension methods with an 80% group approach; direct communication 86.67% and extension methods with a combination of 91.11% senses. The conclusion is that the local wisdom-based extension method is the most effective method with a group approach, direct communication and uses a combination of the senses of acceptance (sight, hearing, touch, taste, and smell).